Students’ Perspectives of Online Collaborative Learning in Professional Narrative Writing Course - Kezia Intan Permani; Listyani - Listyani (SAGA: Journal of English Language Teaching and Applied Linguistics, 2022)
Writing becomes one of the complex processes in learning English. Students must consider many things to develop good writing, especially non-native English students in the Professional Narrative Writing course at Universitas Kristen Satya Wacana. Due to the COVID-19 that was spreading in the world, Professional Narrative Writing students had to do online writing activities, one of them was doing online collaborative learning. Therefore, the aim of this study was to investigate the students’ perspectives of online collaborative learning in the Professional Narrative Writing course. Also, this study attempted to address one research question: What are the students’ perspectives of online collaborative learning in Professional Narrative Writing course?. The participants of this study were thirty-four students from three online Professional Narrative Writing course. This study used the qualitative method with thematic analysis. Then, the data were collected using open-ended and close-ended questionnaires and interviews. The results showed that all students did online collaborative learning in the Professional Narrative Writing course. They had positive and negative feelings during the online collaborative learning. Besides that, the students had different opinions on whether online collaborative learning was beneficial or difficult for them. Although students experienced difficulties in online collaborative learning, they could deal with them well. Afterward, the results indicated the number of students who preferred online collaborative learning was higher than individual work. Hopefully, this research was fruitful for the students to find out other students’ perspectives on online collaborative learning. Also, this research may help the lecturers to determine whether online collaborative learning was suitable for students or not.